Digital Marketing Potential for Umkm Business Development Facilities In Bojonegoro - Rozi, Fahrur; Yusuf, Munawir; Setiawan, Abdul Haris (Universitas Sebelas Maret, 2023)
Digital marketing strategy is one of the activities to promote products to pro-spective buyers, this strategy is quite popular with business people in the dig-ital era. Therefore, this study aims to identify the views of MSME business actors on the potential of digital marketing strategies. Research is a type of quantitative research with surveys, questionnaires used as instruments to col- lect data in the form of responses from MSME actors. A total of 27 MSMEs in Kalitidu Village, Bojonegoro Regency were involved as the subjects of this research. The findings from this research indicate that MSME actors think that digital marketing strategy is a science that they must master so that they can optimize product marketing and sales, although most of them have tried to implement mark eting through social media, and use product distribu-tion channels online but still consider that digital marketing capabilities and strategies still need to be studied in order to obtain greater and optimal results from business activities. Therefore, the use of digital technology-based mar-k eting concepts (digital marketing) provides hope for MSMEs to develop into centers of economic power.